No indications of persistent oxidative stress in response to an Ironman triathlon - Neubauer, O.; König, D.; Kern, N.; Nics, L.; Wagner, K. H. (Medicine & Science in Sports & Exercise, 2008)
Introduction: Training for and competing in ultraendurance exercise events is associated with an improvement in endogenous antioxidant defenses as well as increased oxidative stress. However, consequences on health are currently unclear.